2019
DOI: 10.3389/fevo.2019.00170
|View full text |Cite
|
Sign up to set email alerts
|

Clone Configuration and Spatial Genetic Structure of Two Halophila ovalis Populations With Contrasting Internode Lengths

Abstract: Fine-scale spatial genetic structure (SGS) is predominantly determined by gene flow. While sexually reproducing plants can disperse their genes through pollen and seed grains, clonal plants can additionally disperse genes through clonal growth. Plants' clonal reproduction strategy, however, often varies within and between species. Still, the effect of differential clonal reproduction strategy on fine-scale SGS remains somewhat unclear. Halophila ovalis is a fast-growing clonal seagrass, whose internode length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…These findings indicate that H. ovalis is a species that has high turnover meadows that are maintained through sexual reproduction. Preliminary findings pertaining to genetic diversity in H. johnsonii are in stark contrast to the inferences made for H. ovalis by Xu et al (2019). The availability of microsatellite markers allows further testing of the reproductive biology of H. johnsonii and this study will be the first to use high resolution co-dominant markers to assess genetic diversity in the species.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…These findings indicate that H. ovalis is a species that has high turnover meadows that are maintained through sexual reproduction. Preliminary findings pertaining to genetic diversity in H. johnsonii are in stark contrast to the inferences made for H. ovalis by Xu et al (2019). The availability of microsatellite markers allows further testing of the reproductive biology of H. johnsonii and this study will be the first to use high resolution co-dominant markers to assess genetic diversity in the species.…”
Section: Introductionmentioning
confidence: 67%
“…Microsatellites, the markers of choice for seagrass clonality research (e.g., Arnaud-Haond et al, 2005;McMahon et al, 2014McMahon et al, , 2017 were later developed for H. ovalis (Xu et al, 2010). A subsequent study using these markers found high genetic diversity in two monospecific H. ovalis populations in the Hepu Dugong National Nature Reserve of Guangxi, China and that a small number of genets consisted of multiple ramets (Xu et al, 2019). One of the main findings was that clonal diversity was high and clones were small compared to other seagrass species (e.g., Arnaud-Haond et al, 2012;Bricker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these clones, which are morphologically very similar, are very difficult to distinguish by visual observation [74]. On the other hand, SSR markers have frequently been used in clone analysis of different plant species in recent years, as they are highly informative about the level of heterozygosity between and within grapevine cultivars [75][76][77][78].…”
Section: Clonal Analysismentioning
confidence: 99%